Book Review of “Psychology Through Critical Auto-Ethnography: Academic Discipline, Professional Practice and Reflexive History” - Strong, Tom (Canadian Journal of Counselling and Psychotherapy, 2020)
Ian Parker has been a central figure in the movement that has come to be known as critical psychology. In bringing together deconstructive methods together with social justice concerns, Parker has also criticized the academic and professional norms of psychology, and not without recrimination. I review his most recent and personal book, Psychology through critical auto-ethnography: Academic discipline, professional practice and reflexive history, relating Parker’s narrative, generally, to social justice-minded practitioners and academics.